Mechanical communication-associated cell directional migration and branching connections mediated by calcium channels, integrin β1, and N-cadherin - Ouyang, Mingxing; Zhu, Yiming; Wang, Jiajia; Zhang, Qingyu; Hu, Yanling; Bu, Bing; Guo, Jia; Deng, Linhong (Frontiers in Cell and Developmental Biology, 2022)
Cell–cell mechanical communications at a large spatial scale (above hundreds of micrometers) have been increasingly recognized in recent decade, which shows importance in tissue-level assembly and morphodynamics. The involved mechanosensing mechanism and resulted physiological functions are still to be fully understood. Recent work showed that traction force sensation in the matrix induces cell communications for self-assembly. Here, based on the experimental model of cell directional migration on Matrigel hydrogel, containing 0.5 mg/ml type I collagen, we studied the mechano-responsive pathways for cell distant communications. Airway smooth muscle (ASM) cells assembled network structure on the hydrogel, whereas stayed isolated individually when cultured on glass without force transmission. Cell directional migration, or network assembly was significantly attenuated by inhibited actomyosin activity, or inhibition of inositol 1,4,5-trisphosphate receptor (IP3R) calcium channel or SERCA pump on endoplasmic reticulum (ER) membrane, or L-type calcium channel on the plasma membrane. Inhibition of integrin β1 with siRNA knockdown reduced cell directional migration and branching assembly, whereas inhibition of cell junctional N-cadherin with siRNA had little effect on distant attractions but blocked branching assembly. Our work demonstrated that the endoplasmic reticulum calcium channels and integrin are mechanosensing signals for cell mechanical communications regulated by actomyosin activity, while N-cadherin is responsible for traction force-induced cell stable connections in the assembly.